2021
DOI: 10.1038/s41598-021-82717-z
|View full text |Cite
|
Sign up to set email alerts
|

Free radical degradation in aqueous solution by blowing hydrogen and carbon dioxide nanobubbles

Abstract: The main findings are the hydroxyl radical scavenging and the superoxide anion diminishing by mixing the carbon dioxide (CO2) nanobubbles after hydrogen nanobubble blowing in water and alcohol aqueous solution. The nanobubbles produce the hydroxyl radical by ultrasonic waves, changing the pH and catalyst and so on, while the nanobubble is very reactive to scavenge free radicals. In this research especially hydrogen (4% H2 in argon) and CO2 nanobubbles have been blown into hydrogen peroxide (H2O2) added pure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This reaction agreed with the literature. The existing •OH and •O2 − scavenging was reported by blowing CO2 nanobubbles after blowing H2 nanobubbles [30]. The formation of a monolayer by ethanol [12] and the arrangement of ethanol molecules on interfaces stabilize the bulk nanobubbles [13,14].…”
Section: H2o + H2mentioning
confidence: 97%
See 1 more Smart Citation
“…This reaction agreed with the literature. The existing •OH and •O2 − scavenging was reported by blowing CO2 nanobubbles after blowing H2 nanobubbles [30]. The formation of a monolayer by ethanol [12] and the arrangement of ethanol molecules on interfaces stabilize the bulk nanobubbles [13,14].…”
Section: H2o + H2mentioning
confidence: 97%
“…The radical production by ultrasonic wave irradiation becomes more important to produce the radicals, especially •OH in water, by comparing no irradiation and irradiation [29]. Fujita et al, 2021 reported the •OH scavenging and the •O 2 diminishing by mixing the CO 2 nanobubbles after hydrogen nanobubble blowing in water and alcohol aqueous solution [30]. As described above, the ethanol and water solutions containing nanobubbles have various characteristics and there is a possibility to produce the free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals can be generated via intense sonication processes. However, this can be cancelled out by incorporating CO 2 or H 2 has radical scavengers (Fujita et al, 2021). Ozonised water (Takahashi et al, 2012) and plasma activated water (Gao et al, 2022) both generate nanobubbles with hydroxyl radials (‧OH) and are proposed to be used in wastewater treatment to degrade organic compounds and provide overall disinfection.…”
Section: Free Radicalsmentioning
confidence: 99%
“…Separately, the gas nanobubbles have shown great potential and are therefore only natural to assume that the combination of different gases will enhance their function, allow the possibility of a chain reaction treatment. Fujita et al (2021) tested a combination of gaseous nanobubbles on bacteria, observing that the by first treating the sample with hydrogen nanobubbles, followed by carbon dioxide nanobubbles, they could control the radicals present in the solution. The authors concluded that this can be applied for disinfection.…”
Section: Futurementioning
confidence: 99%
“…In recent years, numerous studies have demonstrated that hydrogen molecules can alleviate hydroxyl radical ( • OH)induced cytotoxicity without affecting physiologically important ROS and produce beneficial effects in many disease models. 10,11 There are several methods of hydrogen delivery into living organisms, including inhalation of hydrogen gas, 12 T h i s c o n t e n t i s injection of hydrogen-saturated saline, 13 and drinking hydrogen water. 14 Among these methods, drinking hydrogen water is the most suitable method of intake of molecular hydrogen for aquatic organisms.…”
Section: ■ Introductionmentioning
confidence: 99%